PENGELOLAAN INFORMASI HUMAS LEMBAGA SENSOR FILM DALAM MENANGANI KONFLIK DI INSTAGRAM TERHADAP FILM MORTAL KOMBAT - Lestari, Dini Ayu; Gelgel, Ni Made Ras Amanda; Suryawati, I Gusti Agung Alit; Damasemil, Calvin (E-Jurnal Medium; Vol 3 No 2 (2022): Jurnal Ilmu Komunikasi Vol 3 No 2 Tahun 2022, 2023)
This study aims to analyze the management of public relations information for film censorship institutions in dealing with conflicts on Instagram against Mortal Kombat films. The Film Censorship Institute is a government agency that has the main task of screening or selecting shows that will be shown on television or on the big screen. The screening is carried out to limit the content contained in the film and classify the film into predetermined criteria. This research uses descriptive qualitative method to analyze the existing problems. Informants in this study were parties from the film censorship agency and also some people who gave negative comments to this institution. The findings show that the handling strategy carried out by LSF goes through four steps starting with understanding the problem that is used as the basis for the actions taken, taking action and communication as a strategy for managing information in dealing with conflict in the Mortal Kombat film on Instagram, and the final step is evaluation. from the previous step and the strategy taken is correct. Meanwhile, regarding the success of this strategy through organizational image management theory, LSF has succeeded in restoring the image of the institution through three stages, namely image formation, image restoration, and image maintenance. Keywords: PR, strategy, conflict